Penurunan konsentrasi logam kromium dengan fotokatalis titanium dioksida (TiO2), dan absorben SiO2-CFA - Joice Dorsila Susana Caroles (Jurnal Kimia Fullerene, 2018)
Decrease in the concentration of chromium metal by photocatalysis process, and adsorption has been done on river water samples. Photocatalysis using TiO2 photocatalyst, while adsorption using SiO2 CFA adsorbent was done with the aim of obtaining a picture of the effectiveness between the use of photocatalysis process and the adsorption process to reduce the concentration of chromium metal. The decrease of chromium metal concentration after photocatalysis, and adsorption for 6 hours was analyzed by AAS. Result of analysis showed decrease of chromium metal concentration through bigger photocatalysis that is 79,30% compared through adsorption only equal to 39,4%.